Analyzing the Impact of Covid-19 on the Oil and Gas Industry: A Case Study of Petronas - Daisy Mui Hung Kee; Nur Amira Liyana; Zhang LuXin; Nur Atikah; Ninie Alwanis; Rozaini Afniza (AIBPM Publisher, 2021)
As a result of the Covid-19 epidemic, every industry in the world has been greatly affected. We took Malaysia's Petronas as an example to analyze how oil and gas industries were impacted by such a difficult international situation. This paper investigated how Covid-19 affected Petronas and how it responded to the sharp drop in oil price. In a questionnaire survey, we listed the problems that Petronas may face in this outbreak.